Estimulación de yemas con sombra en una bananera orgánica - Vivanco Sanmartin, Jinsop Javier (2012)
At El Retiro bud stimulation was investigated in an organic banana objectives were: 1. Determine the effect on growth of the bud between treatments desuckering by stimulation of buds with organic banana shade, 2. Set the percentage of functional roots between treatments, being the treatments: T1 yolk 15 cm tall, shady decaying stem of 40 cm, 15 cm yolk T2 high, shaded decaying stem of 60 cm, 15 cm yolk T3 high, with shadow of decaying stem of 80 cm., T4 yolk 15 cm tall, shady decaying stem T5 yolk 1 m 15 cm high, without shade, being the variables: seedling height at 30, 60 and 90 days after applying the shadow, days of leaf emergence in the pseudostem, thickness of the pseudostem at 90 days after the covered, percentage of functional roots at 90 days after the covered, number of buds and bud height to 90 days after capping. In the batch of banana plants took 25 random com a child of 1 m in height e yolk child 15 cm high, which was placed on the tip of pseudostem pieces 40, 60, 80 cm and 1 mlong. We chose at random five plants per treatment, to record in the child and bud development, both in height and thickness of pseudostem. The percentage of functional roots was determined by analyzing the roots of plants. In the experimental field was applied randomly complement the design. The results yielded high statistical significance in the different variables, demonstrating the effect of acceptable coverage of the buds with stalks of bananas, the best results for treatment T3 (yolk 15 cm high, shaded decaying stem of 80 cm) with respect to absolute control especially in height growth in the percentage of functional roots. The conclusions are: bud stimulation by shading of these with decaying stem segments, caused increased growth in height, diameter and increasing the percentage of functional roots and treatments from stem segments of 80 broken cm, is best accomplished through high rates and averages 96.9 cm 87.8 cm for the different variables